2018
DOI: 10.1534/g3.118.200173
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping by Sequencing of 393 Sorghum bicolor BTx623 × IS3620C Recombinant Inbred Lines Improves Sensitivity and Resolution of QTL Detection

Abstract: We describe a genetic map with a total of 381 bins of 616 genotyping by sequencing (GBS)-based SNP markers in a F6-F8 recombinant inbred line (RIL) population of 393 individuals derived from crossing S. bicolor BTx623 to S. bicolor IS3620C, a guinea line substantially diverged from BTx623. Five segregation distorted regions were found with four showing enrichment for S. bicolor alleles, suggesting possible selection during formation of this RIL population. A quantitative trait locus (QTL) study with this numbe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 57 publications
3
19
0
Order By: Relevance
“…GBS pipeline provided the HapMap file containing 10,424 SNPs but only 979 SNPs were polymorphic SNPs used for linkage map construction. The results were similar toKong et al (2018) andGelli et al (2016) that identified GBS based polymorphic SNP markers in sorghum RIL for linkage map construction with 616 and 642 polymorphic SNPs and the linkage maps spanned 1404.8 and 1641 cM., respectively. The linkage map for this study spanned 1,707.11 cM, which is comparable with previously reported sorghum genetic maps that varied from 603.5 to 2,128(Gelli et al 2016;Jordan et al 2011;Kong et al 2018).…”
supporting
confidence: 84%
See 2 more Smart Citations
“…GBS pipeline provided the HapMap file containing 10,424 SNPs but only 979 SNPs were polymorphic SNPs used for linkage map construction. The results were similar toKong et al (2018) andGelli et al (2016) that identified GBS based polymorphic SNP markers in sorghum RIL for linkage map construction with 616 and 642 polymorphic SNPs and the linkage maps spanned 1404.8 and 1641 cM., respectively. The linkage map for this study spanned 1,707.11 cM, which is comparable with previously reported sorghum genetic maps that varied from 603.5 to 2,128(Gelli et al 2016;Jordan et al 2011;Kong et al 2018).…”
supporting
confidence: 84%
“…The results were similar toKong et al (2018) andGelli et al (2016) that identified GBS based polymorphic SNP markers in sorghum RIL for linkage map construction with 616 and 642 polymorphic SNPs and the linkage maps spanned 1404.8 and 1641 cM., respectively. The linkage map for this study spanned 1,707.11 cM, which is comparable with previously reported sorghum genetic maps that varied from 603.5 to 2,128(Gelli et al 2016;Jordan et al 2011;Kong et al 2018). The average inter-marker distance was 1.74 cM, showing a high quality genetic map using GBS in RIL population.QTLs for flowering time associated with Ma1 and SbEHD1Sorghum flowering time or maturity genes were identified at six loci, designated Ma1 on chromosome 6 (locus name: SbPRR37, Sobic.006G057866; region: 40304883-40316799), Ma2 on chromosome 2 (unknown), Ma3 on chromosome 1 (SbPHYB, Sobic.001G394400: 68034103-68043358), Ma4 on chromosome 10 (unknown), Ma5…”
supporting
confidence: 84%
See 1 more Smart Citation
“…In addition, two associations for plant height observed on chromosome 7 corresponded to qPHT7.1 and Dw3 [16], which were identified using linkage mapping [32][33][34]. Three QTLs detected for plant height, qPH6.1, qPH7.1 and qPH9.1 through QTL mapping [35], have also been found in two GWAS studies [12,36]. However, novel genomic regions are often detected to be associated with traits in each of the unique GWAS studies.…”
Section: Introductionmentioning
confidence: 98%
“…Sorghum is the fifth most agriculturally important cereal crop in regard to global dedicated acreage and production quantity (Gladman et al., 2019). It is also an important biofuel crop and serves as a botanical model for many tropical C4 grasses with complex genomes such as maize and sugarcane (Kong et al., 2018). Sorghum was domesticated in northern Africa about 6,000 years ago, and possesses robust tolerance to drought, heat and high‐salt conditions (Biruma et al., 2012).…”
Section: Introductionmentioning
confidence: 99%